2017
DOI: 10.1016/j.cej.2017.04.096
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective and efficient removal and extraction of heavy metals by layered double hydroxides intercalated with the diphenylamine-4-sulfonate: A comparative study

Abstract: Six new NiCr layered double hydroxides (LDHs) intercalated with different inter-layeranions, including diphenylamine-4-sulfonate (DPA), dodecyl sulfonate (DS), pentansulfonate (PS), terephthalate (TA), fumarate (FA) and 2-ethylhexyl hydrogenphosphate (EHP), were synthesized and used to removal of Cd 2+ , Pb 2+ , Cu 2+ , and Zn 2+ ions from water samples. The maximum adsorption capacities (q m ) for the mentioned LDHs based on their inter-layer anions were DPA>DS>PS>TA>FA>DEHP. This observation highlights the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(24 citation statements)
references
References 47 publications
0
22
0
2
Order By: Relevance
“…247 Therefore, the removal of heavy metals from environmental medium such as water remains a key subject of research. Previous studies suggested that functionalized LDHs exhibit very favorable adsorption to heavy metals as measured by high adsorption capacity and selectivity, 2,66,76,247,[250][251][252] which resulted in effective removal of toxic metals to meet increasingly strict environmental regulations. For example, Ma and coworkers found that the intercalation of MoS4 2into MgAl-LDH interlayer space could not only endow MgAl-LDH with the ability to adsorb various heavy metal ions (Co 2+ , Ni 2+ , Zn 2+ , Cd 2+ , Pb 2+ , Cu 2+ , Hg 2+ , and Ag + ) rapidly and effectively, but also offer high selectivity for some of these heavy metals.…”
Section: Heavy Metals Removalmentioning
confidence: 99%
“…247 Therefore, the removal of heavy metals from environmental medium such as water remains a key subject of research. Previous studies suggested that functionalized LDHs exhibit very favorable adsorption to heavy metals as measured by high adsorption capacity and selectivity, 2,66,76,247,[250][251][252] which resulted in effective removal of toxic metals to meet increasingly strict environmental regulations. For example, Ma and coworkers found that the intercalation of MoS4 2into MgAl-LDH interlayer space could not only endow MgAl-LDH with the ability to adsorb various heavy metal ions (Co 2+ , Ni 2+ , Zn 2+ , Cd 2+ , Pb 2+ , Cu 2+ , Hg 2+ , and Ag + ) rapidly and effectively, but also offer high selectivity for some of these heavy metals.…”
Section: Heavy Metals Removalmentioning
confidence: 99%
“…Asiabi et al prepared different LDH s modified with the diphenylamine-4-sulfonate for the highly selective removal of the heavy metals. Also, they synthesized an Ni/Al LDH intercalated with zwitterionic glycine for the removal of As, Cr, and Se (27). Hu and O'Hare recommended the synthesis of belt-like Mg-Al LDHs modified using tri-block copolymers (28).…”
Section: Introductionmentioning
confidence: 99%
“…mH 2 O] x− , where M II is a divalent cation, M III is a trivalent cation, and A n− is an anion. Their lamellar structure is based on brucite-like sheets, where some divalent cations are replaced with trivalent cations, resulting in some positively charged layers that contain between them various anions such as CO 3 2− , Cl − , NO 3 − , or even organic anions [4,5]. This structure increases their adsorptive properties, especially if the contaminant is in the form of oxyanions [6][7][8].…”
Section: Introductionmentioning
confidence: 99%